The need of Social Librarianship in University Education: Discussions, Tensions and Critical Horizons for Librarian Praxis (La Rivada, 2025)
This essay advocates for the inclusion of Social Librarianship in the university curricula for Library and Information Science programs, particularly at the National University of Misiones (UNaM), emphasizing its absence as a significant educational shortcoming with social, economic, political, and ethical implications.Building on an undergraduate thesis, it explores the transformative role of libraries in contexts of inequality and challenges the technocratic and neutral view of the librarian. Instead, it proposes a critical educational apprach in which the librarian is envisioned as a social actor committed to justice, inclusion, and equitable access to information. The essay calls for a profound curricular reform that acknowledges the social and political dimensions of the profession.
Keywords: Social Librarianship; National University of Misiones; Libraries